2022
DOI: 10.1097/j.jcrs.0000000000000817
|View full text |Cite
|
Sign up to set email alerts
|

Effect of time since primary laser-assisted in situ keratomileusis on flap relift success and epithelial ingrowth risk

Abstract: To assess the association of time since primary laserassisted in situ keratomileusis (LASIK) with flap relift success and risk for epithelial ingrowth (EI) in eyes undergoing flap relift after primary LASIK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…Prior studies evaluating LASIK enhancements after primary LASIK have been published ( Table 3 ) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. At 12 months, 86% and 99% of our eyes had a UDVA of 20/20 or better and 20/40 or better, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior studies evaluating LASIK enhancements after primary LASIK have been published ( Table 3 ) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. At 12 months, 86% and 99% of our eyes had a UDVA of 20/20 or better and 20/40 or better, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…At 12 months, 86% and 99% of our eyes had a UDVA of 20/20 or better and 20/40 or better, respectively. In comparison, 21.1–93.3% of eyes in previous studies had a UDVA of 20/20 or better while 88.2–100% of eyes had a UDVA of 20/40 or better [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Our results showed 4% of eyes that lost one line of CDVA and 0.6% of eyes that lost two or more lines at 12 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We congratulate Chang et al for their clinically relevant and timely study regarding the effect of time after primary laser-assisted in situ keratomileusis (LASIK) on flap relift success and epithelial ingrowth (EI) risk. 1 They concluded that flaps can be successfully relifted up to 22 years after the primary LASIK with low rates of EI. This topic is extremely important to clinicians who perform these surgeries, so we appreciate their dedication to the advancement of this subject.…”
mentioning
confidence: 99%